Morphometric evaluation of gingival overgrowth and regression caused by cyclosporin in rats - Spolidório, L. C.; Merzel, J.; Villalba, H.; Vargas, P. A.; Coletta, R. D.; Almeida, Oslei Paes de (Wiley, 2001)
Cyclosporin A is a selective immunosuppressant, used in organ transplants to prevent graft rejection. Cyclosporin A can cause various side effects including gingival overgrowth. The aim of this work was to evaluate gingival overgrowth of rats treated daily with 10 mg/kg body weight of Cyclosporin A for 60 days, as well as the regression after the interruption of treatment. All rats treated with Cyclosporin A developed gingival overgrowth, with increased thickness of the epithelium, height and width of the connective tissue. The density of fibroblasts and collagen fibers also increased. Five to 90 days after the interruption of treatment with Cyclosporin A, there was a progressive reduction of the gingival volume and of collagen fibers and fibroblast densities. The reduction was more pronounced in the initial periods and after 90 days did not return to the normal values.
Keywords: Cyclosporin A; Gingival overgrowth; Morphometry; Regression; cyclosporin; immunosuppressive agent; animal; gingiva overgrowth; iatrogenic disease; male; pathology; rat; rat strain; remission; Animal; Cyclosporine; Gingival Overgrowth; Immunosuppressive Agents; Male; Rats; Rats, Wistar; Remission, Spontaneous